Proceedings of the 2017 International Conference Advanced Engineering and Technology Research (AETR 2017) 2018
DOI: 10.2991/aetr-17.2018.79
|View full text |Cite
|
Sign up to set email alerts
|

Hu Moment Invariant: A New Method for Hearing Loss Detection

Abstract: This paper proposed a novel hearing loss detection method. Our method first used seven Hu moment invariants to extract features. Afterwards, we used support vector machine to act as the classifier. The 10x5-fold cross validation shows our method yielded an overall accuracy of 77.47± 1.17%. The sensitivities of healthy control, left-sided hearing loss, and right-sided hearing loss are 77.60± 5.72%, 77.60± 4.30%, and 77.20± 5.98%, respectively. In all, our method is effective in hearing loss identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In the SWE+CSO [17] method, the healthy control group (HC), leftsided SNHL(LSHL) and right-sided SNHL(RSHL) was 91.00%, 89.00%, 90.67%, and 90.22%, respectively. The MAF1 of HMI + SVM [13], WE+CSO [14], FRFE + DAG-SVM [15], SWE+ GA [16], and [17] were 76.06%, 84.11%, 94.06%, 89.89% and 90.22%, respectively. In our AlexNet+SVM method, the left SNHL(LSHL), right SNHL(RSHL), healthy control group (HC) and MAF1 were 94.00%, 95.17%, 94.67% and 94.61%, respectively.…”
Section: Comparison To State-of-the-art Approachesmentioning
confidence: 98%
See 3 more Smart Citations
“…In the SWE+CSO [17] method, the healthy control group (HC), leftsided SNHL(LSHL) and right-sided SNHL(RSHL) was 91.00%, 89.00%, 90.67%, and 90.22%, respectively. The MAF1 of HMI + SVM [13], WE+CSO [14], FRFE + DAG-SVM [15], SWE+ GA [16], and [17] were 76.06%, 84.11%, 94.06%, 89.89% and 90.22%, respectively. In our AlexNet+SVM method, the left SNHL(LSHL), right SNHL(RSHL), healthy control group (HC) and MAF1 were 94.00%, 95.17%, 94.67% and 94.61%, respectively.…”
Section: Comparison To State-of-the-art Approachesmentioning
confidence: 98%
“…Through reading the recent papers published by scholars, it is found that scholars have proposed several feasible methods for image classification [12]. Tang, L. et al (2018) [13] proposed the method of combining Hu moment invariant (HMI) and Support Vector Machine. Gao, R. et al ( 2019) [14] used the hearing loss recognition method based on wavelet entropy and cat swarm optimization, Wang, L. et al (2020) [15] suggested hearing loss recognition based on fractional Fourier entropy and direct acyclic graph Support Vector Machine.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the model accuracy of this experiment with other current advanced methods: WE-GA [9], HMI [36] and SVM-PSO [10]. The comparison results are shown in Table 8.…”
Section: Comparison To State-of-the-art Approachesmentioning
confidence: 99%